Early scale-up of antiretroviral therapy at diagnosis for reducing economic burden of cardiometabolic disease in HIV-infected population. (1st May 2020) - Yang, Chun-Ting; Toh, Han-Siong; Liao, Chia-Te; Kuo, Shihchen; Ou, Huang-Tz; Ko, Nai-Ying
Abstract : Objective: The current study aims to assess the effect of early scale-up of antiretroviral therapy (ART) at HIV diagnosis on the economic burden of cardiometabolic diseases (CMDs) in HIV-infected population. Design: Cohort study. Methods: The study cohort comprised 10 693 newly diagnosed HIV patients without CMDs before HIV diagnosis identified from a nationwide HIV cohort in Taiwan. The patients were stratified by ART use [medication possession ratio ≥0.8: (high) vs. <0.8: (low)] and AIDS-defining illnesses (ADI) status [present: (+) vs. absent: (−)] at the first year of HIV diagnosis into four groups: ART (low) and ADI (−), ART (low) and ADI (+), ART (high) and ADI (−), and ART (high) and ADI (+). The economic analysis of incident CMDs was from the perspective of Taiwan's single-payer healthcare system and estimated using generalized estimating equations. Results: CMDs significantly increased annual direct medical costs by 31% (hypertension) to 127% [cardiovascular diseases (CVDs)]. The annual cost burden of diabetes, dyslipidemia, and CVDs in the ART (high) and ADI (−) group significantly decreased by 42, 30, and 31%, respectively, compared with the ART (low) and ADI (+) group. Compared with the ART (low) and ADI (+) group, the annual cost burden of CVDs in the ART (high) and ADI (−) and ART (high) and ADI (+) groups decreased by 31 and 14%, respectively, suggesting increased cost-savings when ART is initiated at diagnosis before ADI occurrence. Conclusion: The early scale-up of ART at diagnosis before ADI occurrence is important for minimizing the economic burden of incident CMDs among HIV-infected patients. Abstract : Supplemental Digital Content is available in the text